Efektivitas Pembelajaran Daring dengan Menggunakan E-learning Madrasah Terhadap Optimalisasi Pemahaman Matematika Siswa - Sutini Sutini; Mohammad Mushofan; Aizza Ilmia; Anisa Dwi Yanti; Annisa Nur Rizky; Siti Lailiyah (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2020)
During the COVID-19 pandemic, the government was requiring to be able to implement a learning system by the applicable health protocol. Based on this, the government must change the learning system from face-to-face meetings to online learning. Technology that is rapidly growing can be advantaged to fully support the online learning process so that the Ministry of Religion Affairs makes an innovation, namely e-learning madrasah media for simplifying the online learning process for all madrasah in Indonesia. This study aims to make readers know the level of effectiveness of online learning using madrasah e-learning to optimize the student understanding of mathematics. This study used a survey method that was conducted online with a quantitative descriptive research type. The results are that online mathematics learning activities using e-learning madrasah are quite efficient, considering that there are still constraints on the ownership of students' equipment and inadequate internet networks, and students are not maximal in absorbing the material provided. However, the advantages we found were the full support provided by the school, teachers, and parents for ongoing learning. Also, learning mathematics using madrasah e-learning is efficient and flexible so that students can carry out learning well.